A series of case studies illustrating the role of flow cytometry in the diagnostic work‐up of myelodysplastic syndromes. Issue 1 (18th February 2022) - Westers, Theresia M.; Saft, Leonie; van der Velden, Vincent H. J.; te Marvelde, Jeroen G.; Dunlop, Alan; Ireland, Robin; Valent, Peter; Porwit, Anna; Béné, Marie C.; van de Loosdrecht, Arjan A.
Abstract: Current guidelines recommend flow cytometric analysis as part of the diagnostic assessment of patients with cytopenia suspected for myelodysplastic syndrome. Herein we describe the complete work‐up of six cases using multimodal integrated diagnostics. Flow cytometry assessments are illustrated by plots from conventional and more recent analysis tools. The cases demonstrate the added value of flow cytometry in case of hypocellular, poor quality, or ambiguous bone marrow cytomorphology. Moreover, they demonstrate how immunophenotyping results support clinical decision‐making in inconclusive and clinically 'difficult' cases.